Hierarchical DSSC structures based on 'single walled' TiO2 nanotube arrays reach a back-side illumination solar light conversion efficiency of 8% - So, Seulgi; Hwang, Imgon; Schmuki, Patrik (Energy and Environmental Science, 2015)
In the present work we introduce a path to the controlled construction of DSSCs based on hierarchically structured single walled, self-organized TiO2 layers. In a first step we describe a simple approach to selectively remove the inner detrimental shell of anodic TiO2 nanotubes (NTs). This then allows controlled well-defined layer-by-layer decoration of these TiO2-NT walls with TiO2 nanoparticles (in contrast to conventional TiO2 nanotubes). We show that such defined multiple layered decoration can be optimized to build dye sensitized solar cells that (under back-side illumination conditions) can yield solar light conversion efficiencies to the extent of 8%. The beneficial effects observed can be ascribed to a combination of three factors: (1) improved electronic properties of the ``single walled'' tubes themselves, (2) a further improvement of the electronic properties by the defined TiCl4 treatment, and (3) a higher specific dye loading that becomes possible for the layer-by-layer decorated single walled tubes.
EAM Import::2019-03-13